Manajemen User Dan Pengelolaan Bandwith Pada Jaringan Hotspot SAR Management Router - Parlindungan Kudadiri; Hamdani Hamdani; Rometdo Muzawi; Yoyon Efendi; Wahyat Wahyat (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The use of the internet is currently an important requirement at the STMIK Amik Riau institution, especially in the fields of administration, service and learning. The whole process of the current hotspot internet network service will be connected to students, lecturers, employees and guests. The user must register the network card device in the form of a MAC address to the admin. However, the current system has many weaknesses, including the use of the internet by lecturers and employees as well as the slow performance of information services, getting uneven internet access, while students do not have free hotspot access. This study aims to solve this problem by implementing user login management and bandwidth using the Queue Tree method with the Peer Connection Queue (PCQ) feature. The management process on the server can limit user traffic in uploading and downloading and bandwidth is divided equally in obtaining internet services. In this study, when a user accesses the internet, it is enough to use NIM, NIDN, NIK and guests are given access by default. This research aims to make it easier to access the internet using both laptops and other devices, to make it easier for users and admins to get and provide internet facilities.